Exploring Sensor Gloves for Teaching Children Sign Language. (5th August 2012) - Ellis, Kirsten; Barca, Jan Carlo
Abstract : This research investigates if a computer and an alternative input device in the form of sensor gloves can be used in the process of teaching children sign language. The presented work is important, because no current literature investigates how sensor gloves can be used to assist children in the process of learning sign language. The research presented in this paper has been conducted by assembling hardware into sensor gloves, and by designing software capable of (i) filtering out sensor noise, (ii) detecting intentionally posed signs, and (iii) correctly evaluating signals in signs posed by different children. Findings show that the devised technology can form the basis of a tool that teaches children sign language, and that there is a potential for further research in this area.